Mokryy lug - Vasilyev, Fyodor Alexandrovich (Академия художеств СССР (Academy of Arts of the USSR), 1951)
Artwork; landscape painting depicting meadow 1951 reproduction of 1872 painting 'Wet meadow' by F. Vasilyev. Original title: Мокрый луг PO-0184